Pemberdayaan IKM Makanan dan Minuman di Kabupaten Malang melalui Program Pelatihan Inovasi Produk Oleh DISPERINDAG - Ananda, Kiki Risqi; Sari, Putri Dewi Permata; Damayanti, Yenie Eva (Pakis Journal Institute, 2025)
The empowerment of Small and Medium Enterprises (SMEs) is a strategic step towards enhancing community welfare and strengthening the regional economy. This community service initiative aims to improve the competitiveness of food and beverage SMEs in Malang Regency through a product innovation training program conducted by the Malang Regency Office of Industry and Trade (DISPERINDAG). The training covers production techniques, product diversification, and the utilization of local raw materials to enhance the added value of SME products. The research method employed is qualitative descriptive, using a documentation study approach. The activities are carried out in several phases, including preparation, training implementation, and evaluation of results. The outcomes indicate that the training positively impacts participants’ understanding and skills in developing innovative products. Participants are able to apply more efficient production techniques and create more appealing product variations. It is hoped that this initiative will enhance the operational capacity of SMEs and strengthen the competitiveness of local products in broader markets.